Performance comparison of temperature sensors for closed cycles operating with supercritical CO2 - Belleoud, Pierre; Anselmi Palma, Eduardo; Chetwynd-Chatwin, Jason; Roumeliotis, Ioannis (DuEPublico, 2023)
Near the critical point of carbon dioxide (CO2), small changes in temperature or pressure can result in large changes in the calculation of its thermodynamic properties, thus the right choice of instrumentation is of importance. This paper addresses the challenges related to CO2 temperature measurement in smalldiameter pipes and assesses different sensors utilizing Cranfield University’s supercritical CO2 test rig capabilities. In order to compare temperature sensor types for supercritical CO2, a test tube has been designed to fit different sizes of temperature probes at the discharge of the transcritical compressors at the sCO2 test rig. Different diameters of thermocouples (0.75 to 4.5 mm), Resistance Temperature Detectors (RTDs) and surface sensors were tested and compared in terms of amplitude and adaptability to sudden temperature changes. Results for different fluid conditions in the supercritical region of CO2 were derived. The use of thermowell is discussed as it can offer a suitable compromise between practicality and ‘internal’ measurements. The results presented in this paper aim to provide a comparison of temperature sensors’ performances for different regimes, transient or steady state.
Keywords: instrumentation; uncertainties; thermocouples; supercritical CO2; transient